Development of the Shallow Water Method to Stimulate Basic Swimming Movements for Children aged 5-6 Years - Iffy Nadya Fahmiruwhanti; Pramono Pramono; Munaisra Tri Tirtaningsih (Budapest International Research and Critics University, 2022)
The objectives of this research are (1) to develop a swimming learning method for early childhood (2) to determine the validity of the method in stimulating basic swimming movements, and (3) to determine the results of the effectiveness of using the method for children. The research of the shallow water method development refers to the Borg n Gall model which is synthesized into six steps according to the research objectives. The data technique used is the result of expert validation and effectiveness testing through experiments with paired t-test statistical data analysis. The results of the development of the shallow water method meet the valid criteria with the results of the expert test of swimming material reaching a validity level of 94%, the result of the expert test of swimming learning 76%, and the practitioner test of 98 %. The field trial of the application of the shallow water method, the results of the pre-test, children got a score of 13.36 and the post-test results got a score of 17. Based on the analysis, the resulting t count is 5.823 and t table is 2.160, meaning that t count > t table. So it can be concluded that there is a significant difference in children's basic swimming skills before and after using the shallow water method. The advice given in the development of the shallow water method is that in using the method when swimming activities/learning should look at the condition of the child and recognize the characteristics of the child because the child's achievement in mastering the level of one child is different from another.